2020
DOI: 10.1371/journal.pntd.0008483
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with Clonorchis sinensis infections in rural communities in northern Vietnam

Abstract: Background Clonorchiasis, caused by the fish-borne trematode Clonorchis sinensis, is a neglected tropical disease and a public health issue in endemic countries. In Vietnam, an in-depth analysis of risk factors for the condition is missing up to now. This study aimed to determine the prevalence of C. sinensis infection and associated risk factors in rural communities in northern Vietnam. Methodology/Principal findings A cross-sectional survey was conducted in 4 communes in Yen Bai and Thanh Hoa provinces where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…The provincial level survey in Guangxi demonstrated a prevalence of 14.0% in male and 7.2% in female in 2019. Consistently, the prevalence in the male was around 2 times than that in the female in local survey in Republic of Korea and Vietnam [35,36]. It was believed that the difference between sexes in C. sinensis infection is mainly related to dietary customs namely raw-fishing eating behavior [7,37,38].…”
Section: Discussionmentioning
confidence: 91%
“…The provincial level survey in Guangxi demonstrated a prevalence of 14.0% in male and 7.2% in female in 2019. Consistently, the prevalence in the male was around 2 times than that in the female in local survey in Republic of Korea and Vietnam [35,36]. It was believed that the difference between sexes in C. sinensis infection is mainly related to dietary customs namely raw-fishing eating behavior [7,37,38].…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, clonorchiasis is endemic in the North region ( Dang et al, 2008 ), where it has been reported in 21 provinces and where more than one million people were estimated to be infected ( Qian et al, 2012 ; Sithithaworn et al, 2012 ). The reported prevalence in humans ranged from 0.2% to 40.4%, and infection is associated with the consumption of raw fish ( De et al, 2003 ; Nguyen et al, 2020b ). On the other hand, O. viverrini infection in humans is endemic in Central Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…Next to its importance for the economy, fish provides a cheap protein source for the Vietnamese population ( Allison, 2011 ). However, the local culinary habit to consume raw fish puts the Vietnamese population at risk for fish-borne zoonoses ( Nguyen et al, 2020b ). At the same time, general consumer expectations and living conditions are progressing, thus leading to an increased demand for safer fish.…”
Section: Introductionmentioning
confidence: 99%
“…The different cost yield in different populations was essentially attributable to the difference in prevalence. Because clonorchiasis shows a significantly differential distribution in different genders and ages due to difference in ingesting raw freshwater fish [ 5 , 25 , 31 ]. Adult male shows a higher prevalence compared to adult female and both show higher prevalence compared to children.…”
Section: Discussionmentioning
confidence: 99%